Corrosion resistance for superwetting immiscible oil/water separation porous materials - Rong, Wanting; Zhang, Haifeng; Tuo, Yanjing; Chen, Weiping; Liu, Xiaowei (RSC advances, 2019)
In this paper, we first fabricate a 3D porous FZCF (FAS-modified ZnO-grown copper foam) with robust superhydrophobicity in air and superoleophilicity under water and the repeatable superwettability, and then mainly explore and analyze its corrosion resistance. The superhydrophobic-superoleophilic FZCF as an immiscible oil/organic solvent separation material shows high adsorption capacity and separation efficiency due to its heterogeneous micro-nano structures and low surface energy. It has excellent corrosion resistance under various pH conditions, and can serve as a corrosion protective barrier that prevents metal from contacting corrosive seawater in marine applications. Adsorbed oils also make superoleophilic FZCF keep its durability and stability after suffering attack in strong acid and alkali environments for a long time. Superwetting porous FZCF material that possesses outstanding excellent corrosion resistance demonstrates potential applications in many industrial fields such as oily wastewater treatment and marine oil spill accidents. Superwetting porous FZCF as immiscible oil/organic solvents separation material that possesses excellent corrosion resistance can be widely applied in many industrial fields such as oily wastewater treatment and marine oil spill accidents.